2020
DOI: 10.4414/smw.2020.20393
|View full text |Cite
|
Sign up to set email alerts
|

The Swiss STAR trial – an evaluation of target groups for sexually transmitted infection screening in the sub-sample of women

Abstract: OBJECTIVES: In Switzerland, universal health insurance does not cover any routine testing for sexually transmitted infections (STIs), not even in individuals at high risk, and extra-genital swabbing is not standard of care. We compared STI prevalence in a multicentre prospective observational cohort of multi-partner women with/without sex work and evaluated associated risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Independent risk factors included participation in group sex. 24 Cara et al 25 also found that group sex behaviours among MSM were related to STIs. Ample evidence shows that the use of new drugs can also increase the risk of STIs.…”
Section: Discussionmentioning
confidence: 97%
“…Independent risk factors included participation in group sex. 24 Cara et al 25 also found that group sex behaviours among MSM were related to STIs. Ample evidence shows that the use of new drugs can also increase the risk of STIs.…”
Section: Discussionmentioning
confidence: 97%
“… 15 However, more than 95% of FSW tested for HCV lived in the German‐speaking part of Switzerland, and only two HCV‐RNA‐positive cases were identified. 15 Additionally, the overall population size after 2011, and overlap with other risk groups (including PWUD and OAT participants) are unknown.…”
Section: Methodsmentioning
confidence: 99%
“…A 2011 estimate from UNAIDS suggests that there were around 20 000 female sex workers (FSW) in Switzerland 14 and a recent publication suggests an HCV‐RNA prevalence of 0.2% (95% CI: 0.0%‐1.3%) among FSW in 2016/2017 15 . However, more than 95% of FSW tested for HCV lived in the German‐speaking part of Switzerland, and only two HCV‐RNA‐positive cases were identified 15 . Additionally, the overall population size after 2011, and overlap with other risk groups (including PWUD and OAT participants) are unknown.…”
Section: Methodsmentioning
confidence: 99%
“…Several test‐and‐treat activities focused on these persons, including a special campaign in a part of Switzerland where many of them reside 37 . Following HCV treatment 1,4,7,10,11 and age‐ and liver‐associated mortality, 9,10 650–900 viraemic persons likely remain. Other foreign‐born persons (except subpopulation (iv)): Among notified cases 4,5,7 and in the SCCS, 10,11 HCV cases among this group were slightly higher than among the Swiss‐born general population; among groups of foreign‐born persons, hardly any cases of HCV were found 38–40 . Based on data in the SCCS, 10 we calculated the HCV prevalence among this group as increased by 39% in comparison with the prevalence among the general Swiss population (FSO).…”
Section: Resultsmentioning
confidence: 99%